Predictors of time to recovery from uncomplicated severe acute malnutrition among 6–59 months children treated in out patient treatment in health posts of Nagele Arsi district: a retrospective cohort study - Ashenafi Tsegaye; Bikila Lencha; Kebede Kumsa (BMC Pediatrics, 2022)
Abstract Background Access to outpatient therapeutic feeding programs (OTP) for all children who have uncomplicated severe acute malnutrition (SAM) remains a global public health priority. Identifying predictors that determine time-to-recovery from severe acute malnutrition optimize therapeutic success. However, reliable evidence on the determinants of time to recovery at health posts was not available in Nagele Arsi district of South Ethiopia. Objective This study was aimed to identify determinants of time-to-recovery from uncomplicated SAM among children aged (6–59) months treated at an OTP in health posts of Nagele Arsi district, Southern Ethiopia. Methods Institutional based retrospective cohort study was conducted among 357 children treated in Negele Arsi district from July1, 2018 to June 30, 2020. The children were selected using simple random sampling from 20 health posts. SAM treatment outcomes were compared against international SPHERE standards. The average time-to-recovery was estimated using Kaplan-Meier survival curve and the independent predictors of time to recovery were determined using multivariable Cox-proportional hazard model. The strength of the association was done using adjusted hazard ratio (AHR) with 95% confidence intervals. Statistical significance was declared at p value < 0.05. The results were presented by text, tables and figures. Result A total of 284 (79.6%) children recovered during follow up. The mean weight gain for recovered children was 4.7 + 2.4 g/kg/day. The median time-to-recovery was 44 days 95% CI (42.7–45.3). Children who received Amoxicillin, AHR =2.574, 95% CI (1.879–3.525); de-wormed, AHR = 1.519, 95% CI (1.137–2.031); received Vitamin A, AHR = 2.518, 95% CI, (1.921–3.301) and new admissions, AHR = 1.823, 95%CI, (1.224–2.715) were more likely to recover. However, those who admitted with non-edema, AHR = 0.256, 95% CI, (0.189–0.346); had cough at admission, AHR = 0.513, 95 CI, (0.366–0.719) and had diarrhea at admission AHR = 0.5, 95% CI, 0.5 (0.350–0.712) were less likely to recover. Conclusion and recommendation The recovery rate was within the acceptable ranges of International Sphere Standards. Those children who had cough and diarrhea should be given due attention from health extension workers and program planners. Appropriate provision of routine medication and timely intervention of co-morbidity are needed to increase chance of early recovery.